The philosophy of equal opportunities: assistive technologies in the context of inclusive higher education in Кazakhstan (Journal of Philosophy Culture and Political Science, 2025)
In the context of the digital transformation of higher education, assistive technologies have become a crucial tool for ensuring inclusivity and implementing the principles of equal opportunities. This article examines AT from a philosophical and anthropological perspective, analyzing their role in creating an accessible educational environment for students with special educational needs. The research employed survey methods, comparative analysis, content analysis of documents, and general logical methods.The study identified key barriers to the integration of assistive technologies in inclusive higher education in Kazakhstan. Despite a moderate level of awareness of AT among faculty members, their practical application remains limited. The main obstacles to the use of AT in the educational process include the lack of specialized training for faculty, incompatibility of technologies with existing IT infrastructure, and limited access to necessary software.The aim of this study is to analyze the role of AT in implementing the philosophy of equal opportunities in inclusive higher education in Kazakhstan, to identify AT used in Kazakhstani universities to support the inclusion of students with special educational needs, and to determine faculty perceptions of the effectiveness of AT in the context of inclusive education.Key words: philosophy of equal opportunities, inclusive higher education, assistive technologies, integration, sustainability